Blown sand movement at Kiskunhalas on the Danube-Tisza interfluve, Hungary - Nyári, Diána; Kiss, Tímea (Journal of Environmental Geography, 2009)
The largest blown-sand area of Hungary is located on the Danube-Tisza Interfluve. Here the most significant aeolian activity took place during the Pleistocene, however the aeolian transformation of the landscape occurred also in the Holocene and even in historical times. The aims of the study were (1) to reconstruct the relief at different historical periods; (2) to determine the periods of sand remobilisation during historical times; (3) to identify the changing of climatic conditions and possible types of human activities enabling aeolian activity and (4) to specify the spatial extension of sand movements. To reconstruct the spatial characteristic of sand and palaeosoil layers a 3Dmodel of the deposits at the archaeological site was created using total station measurements and Surfer 8.0 software. In order to determine the exact time of blown-sand movement optically stimulated luminescence (OSL) measurements (6) were applied. Based on the results, the lowermost sandy-loess layer had a late Pleistocene age, on which sequences of palaeosoils and blown-sand layers were formed during the Holocene. The spatial extension of the palaeosoils and sandy layers suggest that the relief has changed significantly over historical times. The former Pleistocene blowout depression has altered because of both the climatic conditions and the human impact on the environment. Blown-sand movements in historical times filled up the blowout depression. The sand sheets reshaped the original morphology and soil properties. Today the surface is more elevated and even, the site is covered by dry and slightly humic sandy soils.